Development of a vital Signs Simulator for Medical Training - Hernández Cabrera, Diego; Basurto Pensado, Miguel Ángel; Buenabad Arias, Héctor Miguel; Martínez Santos, Antonio Isaías; Blanco Ortega, Andrés (Revista Mexicana de Ingenieria Biomedica, 2025)
This work presents the design and development of a vital signs simulator for medical training, based on LabVIEW, which emulates key physiological variables (heart rate, respiratory rate, blood pressure, body temperature, and oxygen saturation) to practice their real-time interpretation. The program features an adjustable interface with two modes: manual, where the user modifies parameters according to training needs, and preloaded, which simulates anomalies such as tachycardia or hypoxemia with a single button. Its operator-user architecture differentiates the interfaces, optimizing system management for the operator and the learning experience for the user. Initial tests with nursing students showed notable improvements in anomaly identification, though without formal statistical validation. This simulator prioritizes the simulation of clinical scenarios. However, its reliance on predefined or manual configurations limits its adaptability to unanticipated situations. This tool enhances the training of students and healthcare professionals in monitoring vital signs in controlled environments.